2019
DOI: 10.1177/2054358119828386
|View full text |Cite
|
Sign up to set email alerts
|

Variation of High-Sensitivity Troponin T Results in Patients Undergoing Continuous Renal Replacement Therapy

Abstract: Background:Cardiac troponins are the preferred biomarker to diagnose myocardial injury. Complicating the interpretation of serial troponins in patients with end-stage renal disease, it has been shown that the hemodialysis procedure results in a small but significant decline in high-sensitivity cardiac troponins (hs-cTnT). This raises the possibility that continuous renal replacement therapy (CRRT) might similarly alter cardiac troponin levels and affect their interpretation when cardiac ischemia is being consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This is in agreement with previous studies, which reported higher than normal hs‐cTnT levels in 90%–100% of hemodialysis patients 20,21,25,28,29,36–38 . Also in agreement with earlier studies, our data show that hs‐cTnT levels diminish significantly during dialysis, with mean diminution ranging from 10% to 15% 38–41 . There was high individual variation in the mean annual predialysis hs‐cTnT concentrations in our patients, with mean levels ranging from 24 ± 2 ng/L to 241 ± 28 ng/L, that is, 10‐fold higher.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies, which reported higher than normal hs‐cTnT levels in 90%–100% of hemodialysis patients 20,21,25,28,29,36–38 . Also in agreement with earlier studies, our data show that hs‐cTnT levels diminish significantly during dialysis, with mean diminution ranging from 10% to 15% 38–41 . There was high individual variation in the mean annual predialysis hs‐cTnT concentrations in our patients, with mean levels ranging from 24 ± 2 ng/L to 241 ± 28 ng/L, that is, 10‐fold higher.…”
Section: Discussionsupporting
confidence: 93%
“… 20 , 21 , 25 , 28 , 29 , 36 , 37 , 38 Also in agreement with earlier studies, our data show that hs‐cTnT levels diminish significantly during dialysis, with mean diminution ranging from 10% to 15%. 38 , 39 , 40 , 41 There was high individual variation in the mean annual predialysis hs‐cTnT concentrations in our patients, with mean levels ranging from 24 ± 2 ng/L to 241 ± 28 ng/L, that is, 10‐fold higher. Conversely, mean creatine kinase (both CK and CK‐MB) concentrations remained within normal range during the study year.…”
Section: Discussionmentioning
confidence: 66%